Futures and Beyond: Creativity and 4IR Conference 2022 - Alex Halligey (UJ Press, 2023)
FUTURES & BEYOND and 4IR Virtual Conference was hosted online by UJ Arts & Culture on 30 and 31 August 2022. The University of Johannesburg has positioned the Fourth Industrial Revolution (4IR) as its visionary focus in research and higher education, and UJ Arts & Culture, as a division of the Faculty of Art, Design and Architecture (FADA), has been facilitating an ongoing discussion on how thinking around the notion of the 4IR connects to the creative industries, specifically within the South African context and African continental context more broadly. The Futures and Beyond conference was an entirely new initiative coming out of this discussion. The thematic approach to the conference was divided into two streams, with one being ethics, intellectual property, and technology, and the other being creative industries, innovation, and development.